Modelling radiation damage to pixel sensors in the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Bolz, Arthur; Brandt, Oleg; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Helary, Louis; Jongmanns, Jan; et al. (Journal of Instrumentation, 2019)
Silicon pixel detectors are at the core of the current and planned upgrade of the ATLAS experiment at the LHC. Given their close proximity to the interaction point, these detectors will be exposed to an unprecedented amount of radiation over their lifetime. The current pixel detector will receive damage from non-ionizing radiation in excess of 1015 1 MeV neqcm2, while the pixel detector designed for the high-luminosity LHC must cope with an order of magnitude larger fluence. This paper presents a digitization model incorporating effects of radiation damage to the pixel sensors. The model is described in detail and predictions for the charge collection efficiency and Lorentz angle are compared with collision data collected between 2015 and 2017 (10151 MeV neqcm2).
Published 11 June 2019
ATLAS Collaboration: M. Aaboud, C.F. Anders, V.Andrei, C. Antel, A.E. Bolz, O. Brandt, M. Dunford, D.E. Ferreira de Lima, S. Franchino, L. Helary, J. Jongmanns, M. Kolb, A. Kugel, H. Meyer Zu Theenhausen, F. Napolitano, M. Sahinsoy, A. Schoening, H-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, J. Wang, S.M. Weber, M. Wessels, X. Yue [und weitere]
Gesehen am 05.02.2020